Defeat of sugar beets by cercosporosus in short-term fruit-bearing crop rotation for different doses of fertilizers under cultivation - Цвей, Я. П.; Тищенко, М. В.; Філоненко, С. В.; Ляшенко, В. В. (Scientific Progress & Innovations, 2018)
Diseases of sugar beet cause significant damage to beet-eating farms, because potential losses from them can exceed 20 %, and in some years – up to 50–60 % or more. In order to prevent significant deficiencies and losses of sugar beet crops, considerable attention should be paid to timely diagnosis of diseases in plants, to know the bioecological features of the development of their pathogens, the source of primary and secondary infections. It will enable the scientifically substantiated implementation of protective measures that improve the culture and are aimed at limiting and preventing the deve-lopment of individual diseases during plant growth. All it testifies to the relevance of research into the effects of various doses of fertilizers introduced on sugar beet, on the damage to plants of this culture by a clercosporosis, which is considered one of the most common leafy diseases of beets in the zone of insufficient moisture. The article presents the results of studies on the effects of various doses of fertilizers introduced on sugar beet, on the infestation of plants of culture by cercosporosus in short-term fruit-bearing crop rotation. It was established that in the zone of insufficient humidification in the conditions of South-Eastern Forest-Steppe for growing sugar beet in short-rotation fertile crop rotation for application at sugar beet fertilizers at doses of 25 t/ha of manure + N180Р240К180 kg/ha d.r. mineral fertilizers, 25 t/ha manure + N135Р180К135 kg/ha d.r. mineral fertilizers and 50 t/ha manure + N90P120K90 kg/ha d.r. the mineral fertilizers, the intensity of the development of cercosporosus was significantly lower compared to the control without fertilizers, respectively, 51.9, 48.1 % and 50.0 % vs. 68. 1%.